2010
DOI: 10.1158/0008-5472.can-09-2370
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 Elevation in the Prostate Promotes Proliferation and Cooperates with PTEN Loss to Drive Tumor Formation

Abstract: Developmental pathways have been shown to be important in the initiation and progression of cancer in various tissues. We showed that the transcription factor SOX9 is expressed in the epithelia of the mouse embryonic prostate and is required for proper prostate development. We have performed an in vivo investigation into the role of SOX9 in prostate cancer in mouse and human. Studies on Pten and Nkx3.1 mutant mice show that cells with an increased level of SOX9 appear within the epithelia at the early stages o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 31 publications
11
123
0
Order By: Relevance
“…But the expression level of SOX9 in PCa tissues were higher than that in adjacent benign prostate tissues (IRS: PCa = 7.16 ± 0.228 vs. Benign = 5.96 ± 0.461, p  = 0.041) significantly (Figure 2). The SOX7 and SOX9 expression occurred mainly in the nucleus, while SOX10 in the cytoplasm, which is similar to the results from the previous studies [10,12]. Representative pictures of immunohistochemistry staining of SOX7, SOX9 and SOX10 are shown in Figure 3.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…But the expression level of SOX9 in PCa tissues were higher than that in adjacent benign prostate tissues (IRS: PCa = 7.16 ± 0.228 vs. Benign = 5.96 ± 0.461, p  = 0.041) significantly (Figure 2). The SOX7 and SOX9 expression occurred mainly in the nucleus, while SOX10 in the cytoplasm, which is similar to the results from the previous studies [10,12]. Representative pictures of immunohistochemistry staining of SOX7, SOX9 and SOX10 are shown in Figure 3.…”
Section: Resultssupporting
confidence: 88%
“…In 2007 and 2008, Wang et al [7,8] also demonstrated that SOX9 was expressed in PCa cells and was increased in relapsed hormonerefractory PCa. In 2010, Thomsen et al [12] identified SOX9 as part of a developmental pathway that is reactivated in prostate neoplasia where it promotes tumor cell proliferation. All these previous studies were similar to the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models with specific loss of Pten in combination with other genes have unravelled prostate cancer modulators, such as TRP53, SMAD4 and JNK. 4,6,9,3,[27][28][29] We show here that JunB limits tumour progression of Pten-deficient prostate neoplasia as the loss of Junb, even in few cells, is sufficient to promote invasiveness.…”
Section: Discussionmentioning
confidence: 59%
“…Sox9 sustains the survival of neurofibromatosis tumor cell lines (Miller et al, 2009). Sox9 is expressed in the prostate epithelia and promotes prostate tumor cell proliferation and cooperates with Pten loss to drive tumor formation (Thomsen et al, 2010 floxdel/floxdel chondrocytes. Thus, the chondrocytespecific anti-apoptotic mechanism includes PI3K-Akt pathways that are activated by Sox9 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that increased apoptosis in the terminal mature chondrocytes of 11Prom-Cre mice might reflect an acceleration of the whole process of terminal maturation, including their removal via apoptosis. Because Sox9 does not appear to increase phosphoAkt levels in the prostate (Thomsen et al, 2010), the mechanisms by which Sox9 sustains cell survival might differ between tissues.…”
Section: Discussionmentioning
confidence: 99%